Stress fracture influences bone resorption marker (u-NTX) in female long distance runners - Fujita, S.; Sakuraba, K.; Kubota, A.; Wakamatsu, K.; Koikawa, N. (International Journal of Sports Medicine, 2017)
In this study, we aim to clarify the influence based on bone resorption markers at onset of stress fracture. Also, we will clarify the state of the bone resorption markers of female long distance runners who have a history of stress fracture and also ones who routinely practices running long distances. Participants comprised 19 female long distance athletes. The survey period was 2011-2014, and we measured u-NTX as a bone resorption marker at least twice a year, taking the mean±SD of the periodic measured values without stress fracture as the mean value. Measurements were collected sample when stress fractures developed. 132?u-NTX measurements were taken from 19 participants. As a result, the average was 41.03±12.31?nmolBCE/mmolCRE (Q1: 33.15, Q2: 40.55, Q3: 47.95). In six of the 19 participants, u-NTX could be measured following a stress fracture. The mean value of u-NTX for those participants was 40.16±9.10?nmolBCE/mmolCRE, increasing to 64.08±16.07?nmolBCE/mmol CRE with the stress fracture (p<0.01). The findings showed that, in adult female long distance runners, u-NTX values when there was no stress fracture were within the standard value for mean premenopausal women, but increased when the athletes suffered from a stress fracture.